The effect of virtual events implementations towards behavioural intention of millennials and z generation in Indonesia - Radissa Maharani; Nurdin Sobari (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
To increase the productivity of the business event industry, event holders who have experienced restrictions during the first wave of the COVID-19 pandemic have decided to shift all types of activities onto the digital field. This paper was made to examine the meaning behind the shifting of virtual events and the impact it made on the Millennials and Z generations’ behavioral intention in Indonesia. Considering the level of interest and susceptibility to technology, it can be assumed that the millennials and Z generations are superior to other generations in this matter. This paper focused on the importance of online event communication, engagement, interaction, and its relation to online event experiences, which may affect consumer satisfaction that leads to consumer behavior. The model in this paper uses samples of 230 respondents of Millennials and Z Generations in Indonesia that have attended virtual (online) events in the last three years. Structural equation modeling is used to analyze the data. The results show a positive relationship between Online Consumer-to-Consumer Interaction, Online Content Engagement, and Effective Communication to Online Event Experiences that affects Visitor Satisfaction. So that visitors of virtual events have positive Behavioral Intentions toward the virtual event. The findings of this paper may anticipate the future of implementing virtual events in any business-related industries, more so in the tourism business industry in Indonesia.